Dego's disease in a female child with Anti-Scl-70 antibody positivity - Jigna Krunal Padhiyar; Nayan H Patel; Trusha P Gajjar; Mansi D Buch (Wolters Kluwer Medknow Publications, 2018)
Degos' disease (DD) also known as malignant atrophic papulosis is considered to be a disorder of abnormal coagulation with obliterative arteritis. Its association has been described with connective tissue disorders, human immunodeficiency virus infection (HIV) and wegener's granulomatosis. Gastrointestinal, neurological, ocular, cardiovascular, and pulmonary involvement can also occur in DD. Benign version of DD with only cutaneous manifestations has been described. We are presenting a case of 7-year-old female with multiple irregular-shaped crusted tender lesions with porcelain white scars of healed lesions mainly over the trunk and upper limb and few lesions involving face and legs for the last 6 months. There was a history of occasional headache. Other systemic examination by experts was within normal limit. On further investigation, antinuclear antibody, and anti-Scl-70 antibody were positive with histopathology suggestive of DD. The patient had reduced peak expiratory flaw rate (PEFR). The patient was given oral prednisolone without much improvement. With oral aspirin for a month, the patient had mild improvement. The patient is presently under follow-up for future systemic involvement and response to therapy. Anticipated mortality in DD is 50%-60%. Earlier diagnosis and proper management at such a younger age might benefit the patient; however, they need to be followed up for complications. DD is very rare and very few cases have been reported in children. Ours is unique with anti-Scl-70 antibody positivity.